THE COMPLEXITIES OF TEACHING SKILLS IMPROVEMENT PROGRAM IN INDONESIA - Mangasa Aritonang (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This study investigates the complexities of a teacher training course designed by the Ministry of Education and Culture as a program to improve the teaching skills of teachers. A teacher training program, called Teaching Competency Improvement Program, was conducted as a part of continuing professional development for Indonesian teachers. This training program involved teachers as the facilitators who had attended a one-week training of trainers (ToT) prior to their duties as facilitators. Only those who passed the post test in the ToT were entitled to act as training facilitators. Each facilitator facilitated ten to twenty teacher colleagues in their respective zones following IN1-IN2-ON1-IN3-ON2- IN4-ON3-IN5 pattern for duration of 82 contact hours. This study involved 89 facilitators as respondents to an online survey. Data was gathered and analyzed using qualitative descriptive method. The finding of the study includes problems in the technological tools used in the training program, the time management, the content of the training, coordination problem among parties, and the effectiveness of the training program.